CROSSROADS BETWEEN MUSLIM SPIRITUALITY AND ENVIRONMENTAL SUSTAINABILITY - Bensaid, Benaouda (Journal of Al-Tamaddun, 2018)
The inherent argument in the study is that spirituality helps refine Muslims’ introspective and extrospective awareness and conception towards earth stewardship, extending the capacity for development and environmental sustainability. This study examines the pathways through which spirituality contributes to cultivating and promoting deeper awareness of sustainability and responsibility towards nature among Muslims, with inherent potential for catalyzing action on declining environmental conditions. This conceptual paper draws on the Muslims sources to discuss the framework according to which spirituality re-wires Muslims’ perceptions, attitudes and decision-making vis-à-vis the management of natural resources. This study concludes that Muslim spirituality brings forward relevant prospects to re-conceptualizing and re-packaging environmental sustainability and sustainable development in a multicultural and global context. Further research is essential to investigate potential added value by Muslim spiritual capital to a global agenda of sustainability and to cross-cultural environmental development.